Everyday Time: The Triumph of Each Day in Julieta Dobles’ Los pasos terrestres - Palacios Robles, María de los Ángeles (2014)
The poems, The terrestrial steps, Julieta Dobles Izaguirre contains a poem that includes and reappraises the everyday aspects of existence. It includes the qualities of the time that print you the pace to the experience of every day. Every day is the sign that used to point out that life experiences are carried out in daily living, that experience is also the everyday events of life itself divided into morning, afternoon and evening, as well as life passes by childhood, adulthood an old age.Every day is the time confluence of multiple temporalities, biological, psychological, linear and cyclic time where “Today” is a timeless and fleeting moment.